Inflammatory markers as predictors of liver fibrosis in type 2 diabetes patients with metabolic dysfunction-associated fatty liver disease - Yange Tang; Yulong Deng; Gengliang Zhang; Yanjun Wang; Jing Wang; Jie Wu; Mengjin Gu (Frontiers in Endocrinology)
ObjectiveThis study investigates the link between inflammatory markers and liver fibrosis in type 2 diabetes mellitus (T2DM) patients with metabolic dysfunction-associated fatty liver disease (MAFLD).MethodsFrom Oct 2020 to Oct 2024, 769 hospitalized T2DM patients were studied. They were split into Control (n=389) and Experimental groups (T2DM with MAFLD, n=380). The Experimental group was further divided based on FIB-4 scores into non-fibrosis (FIB-4< 1.3, n=267), suspected fibrosis (1.3 ≤ FIB-4 ≤ 2.67, n=99), and advanced fibrosis (FIB-4 > 2.67, n=14). Logistic regression identified factors affecting liver fibrosis, while ROC analysis assessed the predictive value of NLR, SIRI, PLR, and PHR for liver fibrosis in T2DM-MAFLD patients.ResultsThe Experimental group showed higher BMI, FPG, TG, TC, LDL-C, ALT, AST, ALB, GGT, and SUA, but lower age, diabetes duration, MPV, and HDL-C (P< 0.05). Compared to non-fibrosis, suspected fibrosis had higher age, diabetes duration, MPV, AST, and NLR, and lower LY, PLR, PHR. Advanced fibrosis featured higher age, AST, NLR, FPG, HbA1c, SIRI, and lower LY, RBC, LDL-C, PLR, PHR, Hb, PLT, and ALB (P< 0.05). Logistic regression identified NLR, SIRI, PLR, and PHR as significant factors for liver fibrosis. ROC analysis showed AUCs of 0.712 (NLR), 0.757 (SIRI), 0.703 (PLR), and 0.806 (PHR) with sensitivities and specificities varying among markers. Optimal cut-offs were 1.573 (NLR), 1.465 (SIRI), 110.819 (PLR), and 185.379 (PHR).ConclusionsNLR, SIRI, PLR, and PHR significantly influence liver fibrosis in T2DM patients with MAFLD, aiding in its diagnosis and management.